MGMT promoter methylation status and MGMT and CD133 immunohistochemical expression as prognostic markers in glioblastoma patients treated with temozolomide plus radiotherapy - Melguizo, Consolación (BioMed Central, 2012)
BACKGROUND: The CD133 antigen is a marker of radio- and chemo-resistant stem cell populations in glioblastoma (GBM). The O(6)-methylguanine DNA methyltransferase (MGMT) enzyme is related with temozolomide (TMZ) resistance. Our propose is to analyze the prognostic significance of the CD133 antigen and promoter methylation and protein expression of MGMT in a homogenous group of GBM patients uniformly treated with radiotherapy and TMZ. The possible connection between these GBM markers was also investigated. METHODS: Seventy-eight patients with GBM treated with radiotherapy combined with concomitant and adjuvant TMZ were analyzed for MGMT and CD133. MGMT gene promoter methylation was determined by methylation-specific polymerase chain reaction after bisulfite treatment. MGMT and CD133 expression was assessed immunohistochemically using an automatic quantification system. Overall and progression-free survival was calculated according to the Kaplan–Meier method. RESULTS: The MGMT gene promoter was found to be methylated in 34 patients (44.7%) and unmethylated in 42 patients (55.3%). A significant correlation was observed between MGMT promoter methylation and patients’ survival. Among the unmethylated tumors, 52.4% showed low expression of MGMT and 47.6% showed high-expression. Among methylated tumors, 58.8% showed low-expression of MGMT and 41.2% showed high-expression. No correlation was found between MGMT promoter methylation and MGMT expression, or MGMT expression and survival. In contrast with recent results, CD133 expression was not a predictive marker in GBM patients. Analyses of possible correlation between CD133 expression and MGMT protein expression or MGMT promoter methylation were negative. CONCLUSIONS: Our results support the hypothesis that MGMT promoter methylation status but not MGMT expression may be a predictive biomarker in the treatment of patients with GBM. In addition, CD133 should not be used for prognostic evaluation of these patients. Future studies will be necessary to determine its clinical utility.